Lipid peroxidation and antioxidant system in menopausal women with insomnia - N. V. Semyonova (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
According to the current data, most menopausal women have reduced life quality and one of the main criteria is sleep quality. It is well known, that sleep loss may cause oxidative stress. The aim of this study was to assess lipid peroxidation and antioxidant system in postmenopausal women with insomnia. Materials and methods: 41 postmenopausal women (18 patients with insomnia, 23 women without insomnia (control)) were examined. Sleep disorders were assessed by using sleep questionnaire (Stanford Sleep Research Center, USA), Epworth Sleepiness Scale, Insomnia Severity Index. The materials for biochemical studies were blood plasma and red cells. Lipid peroxidation and antioxidant system parameters by spectrophotometric and fluorometric methods were determined. Statistical analysis was performed by non-parametric test. The study results showed increase primary products levels in patients with insomnia compared with the control group. Main and control group antioxidant system parameters have no differences. Oxidative stress coefficient in group with insomnia higher than control. Conclusions: insomnia in postmenopausal women is associated with the development of oxidative stress.